Do we need cardiac arrest centres in Australia? - Stub, D.; Bernard, S.; Smith, K.; Bray, Janet; Cameron, P.; Duffy, S.; Kaye, D. (2012)
The mortality rate post admission to hospital after successful resuscitation from out-of-hospital cardiac arrest is high, with significant variation between regions and individual institutions. While prehospital factors such as age, bystander cardiopulmonary resuscitation and total cardiac arrest time are known to influence outcome, several aspects of post-resuscitative care including therapeutic hypothermia, coronary intervention and goal-directed therapy may also influence patient survival. Regional systems of care have improved provider experience and patient outcomes for those with ST elevation myocardial infarction and life-threatening traumatic injury. In particular, hospital factors such as hospital size and interventional cardiac care capabilities have been found to influence patient mortality. This paper reviews the evidence supporting the possible development and implementation of Australian cardiac arrest centres.